2018
DOI: 10.2147/idr.s157847
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm infections between Scylla and Charybdis: interplay of host antimicrobial peptides and antibiotics

Abstract: PurposeThe aim of this study is to improve the anti-biofilm activity of antibiotics. We hypothesized that the antimicrobial peptide (AMP) complex of the host’s immune system can be used for this purpose and examined the assumption on model biofilms.MethodsFLIP7, the AMP complex of the blowfly Calliphora vicina containing a combination of defensins, cecropins, diptericins and proline-rich peptides was isolated from the hemolymph of bacteria-challenged maggots. The complex interaction with antibiotics of various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Unlike many conventional antibiotics, AMPs are capable of acting on metabolically inactive bacteria, since a main target of their action is bacterial membranes; this could be successfully exploited for the elimination of persister cells in combination with conventional drugs, which has been demonstrated by the synergistic interaction of the latter with AMPs against biofilms (Pletzer and Hancock, 2016;Chernysh et al, 2018). It was shown that various AMPs on their own not only eliminate planktonic bacteria, but also weaken the primary adhesion of bacterial cells to the surface, and within the established biofilms can impair the interaction of the elements of extracellular matrix and embedded bacterial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike many conventional antibiotics, AMPs are capable of acting on metabolically inactive bacteria, since a main target of their action is bacterial membranes; this could be successfully exploited for the elimination of persister cells in combination with conventional drugs, which has been demonstrated by the synergistic interaction of the latter with AMPs against biofilms (Pletzer and Hancock, 2016;Chernysh et al, 2018). It was shown that various AMPs on their own not only eliminate planktonic bacteria, but also weaken the primary adhesion of bacterial cells to the surface, and within the established biofilms can impair the interaction of the elements of extracellular matrix and embedded bacterial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, AMPs extracted from C. vicina larval haemolymph were applied in environments extremely contaminated by germs forming biofilms (under in situ and in vitro conditions), exhibiting strong destructive activity of the matrix and of bacteria adhered to it, these bacteria were resistant to conventional antibiotics, such as Escherichia coli, Staphylococcus aureus , and Acinetobacter baumannii ( Gordya et al, 2017 ). Likewise, this AMP complex containing a combination of defensins, cecropins, diptericins and proline-rich peptides, and interacting synergistically with antibiotics of various classes, produced a much stronger action on the bacterial strains ( Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Klebsiella pneumoniae , and Acinetobacter baumannii ) and the biofilm materials, when compared with the antibacterial effect on the same strains in a model of planktonic cultures ( Chernysh et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…As reported in previous studies, in general, aerobic Gram-negative (G-) bacteria are resistant to clindamycin, but clindamycin is effective against the Gram-positive (G+) bacteria, such as S. aureus, Streptococcus pyogenes, S. pneumoniae, and Streptococcus viridans. The synergistic effect of clindamycin combined with AMPs has been reported previously (Spizek et al, 2004;Nguschwemlein et al, 2014;Chernysh et al, 2018). For the G+ bacteria, when clindamycin was used in combination with the AMPs cyclooctapeptides (CPs, including CPs 1-3, 5-7, 10, 11) against S. aureus, all combinations showed partial synergistic effects (0.5 ≤ FICI < 1) (Nguschwemlein et al, 2014).…”
Section: Discussionmentioning
confidence: 56%
“…For the G+ bacteria, when clindamycin was used in combination with the AMPs cyclooctapeptides (CPs, including CPs 1-3, 5-7, 10, 11) against S. aureus, all combinations showed partial synergistic effects (0.5 ≤ FICI < 1) (Nguschwemlein et al, 2014). When clindamycin was used in combination with FLIP7, the AMP complex from the blowfly Calliphora vicina contains a combination of defensins, cecropins, diptericins, and proline-rich peptides against S. aureus, showing a synergistic effect (Chernysh et al, 2018). To FIGURE 6 | Effect of Sph 12−38 in combination with rifampin and azithromycin, respectively, on wound healing in vivo.…”
Section: Discussionmentioning
confidence: 99%